Evaluation of the early weigh-in policy for mixed martial arts events adopted by North American athletic commissions. Issue 1 (2nd January 2022) - Curran-Sills, Gwynn; Levitan, Mark; Yeasmin, Fahmida
ABSTRACT: Objective: To characterize the epidemiology of overweight athletes before and after the introduction of the Early Weigh-In Policy (EWIP). Methods: A retrospective cohort study examined the weigh-in results for professional mixed martial arts (MMA) events over a 2-year period around the introduction of the new EWIP between 2014 and 2018. Descriptive statistics were used to characterize the study populations. Risk ratios were used to identify differences in the study populations before and after the introduction of the EWIP. Results: After the introduction of the EWIP, the number of overweight athletes increased from 5.7% to 8.4% and the average overweight mass increased from 1.3 kg (2.9 lbs) to 1.8 kg (3.9 lbs) [difference, 0.5 kg (1.0 lb), p = 4.35 × 10^(−5)]. The proportion of athletes is not distributed similarly across the different overweight mass categories when comparing the pre- and post-EWIP time frames ( p = 0.006). More athletes in the pre-EWIP period were overweight by smaller amount, while in the post-EWIP period athletes were overweight by larger amount. Of the athletes who were overweight before the regulation change, 28.7% were over the weight limit by greater than 1.8 kg (4 lbs), compared to 39.5% after the new EWIP introduction. On average, the ratio of overweight athletes per events by commission was 1.2 before the introduction of the EWIP and 2.1 after. Conclusion: These results appear to indicate that the EWIP has not altered weight-cutting culture in MMA in a positive manner. This study casts doubt on the benefits of an EWIP and raised the possibility of utilizing the longitudinal weight monitoring approach to mitigate rapid weight-cycling behavior. However, before additional changes are made by any athletic commission, further research is needed to examine the efficacy of the abovementioned longitudinal weight monitoring approach or any other strategy.